Inflation is not an Effective Remedy for High Public Debt Ratio - Michael Grömling; Jürgen Matthes (Wirtschaftsdienst)
Abstract Economies around the world are facing high price increases. Inflation affects government budgets as well as the sustainability of public debt. How and to what extent is the public debt ratio affected by higher inflation rates? High inflation is not a lasting remedy for a high public debt ratio. Only under very specific conditions — and by simultaneously ignoring the manifold knock-on effects of inflation — does a higher inflation rate bring about a decline in the government debt ratio. In the longer term, it may be dangerous if inflation expectations are de-anchored and interest rates rise for a prolonged time so that debt sustainability is ultimately jeopardised.